1995
DOI: 10.1364/josaa.12.002252
|View full text |Cite
|
Sign up to set email alerts
|

Disability glare: effects of temporal characteristics of the glare source and of the visual-field location of the test stimulus

Abstract: One of the main early complaints of cataract patients, even when these patients exhibit only mild glare problems as measured by standard tests, is that glare impairs their night driving. To provide a better measure of the patients' impairment, glare tests should include measurements of the glare effect in conditions more similar to those found in night driving. During night driving the ambient light is very low, and oncoming headlights present a transient temporal pattern. Furthermore, the objects of interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
13

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
1
14
1
13
Order By: Relevance
“…The studies of driving crashes indicate that alcohol interacts with stroboscopic glare to create particularly high risks of crash. The published studies propose that stroboscopic glare effects of lights in tunnels and headlights at night are related to drunken driver accidents [12]. Our studies have shown that a subject's ability to recover after exposure to glare is diminished progressively by consumption of alcohol.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…The studies of driving crashes indicate that alcohol interacts with stroboscopic glare to create particularly high risks of crash. The published studies propose that stroboscopic glare effects of lights in tunnels and headlights at night are related to drunken driver accidents [12]. Our studies have shown that a subject's ability to recover after exposure to glare is diminished progressively by consumption of alcohol.…”
Section: Introductionmentioning
confidence: 48%
“…By assessing the visual functions of a driver during driving in a real traffic situation under various circumstances of weather and illumination (daytime, dusk, nighttime, city traffic, country road), the limits of adaptation to luminance, object size, object contrast and color can be quantitatively determined. For the glare situation, typical values of glare angle and corneal illuminance of the glare light and the induced reduction of contrast can be determined with a potent glare disability test [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Discomfort glare can be distracting but does not necessarily impair vision, whereas disability glare causes impaired vision (Abrahamsson and Sjostrand 1986;Bullough et al 2002;Mainster and Timberlake 2003). Disability glare is the result of forward intraocular light scattering due to a nearby glare source and leads to a decreased VA and contrast sensitivity (Bichao et al 1995;Bullough et al 2002;Puell et al 2004;Rubin et al 2001).…”
Section: Glare Sensitivitymentioning
confidence: 99%
“…In general, the effect of glare will increase with an increasing glare source, decreasing background luminance, and decreasing angle between the line of sight and the direction of the light source (Bichao et al 1995;Bullough et al 2002). Sivak and Olson (1982) showed a significant disability glare effect if the angle of the glare source is very small (0.2…”
Section: Glare Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation